Farmakogenomik dan Variasi Antar Etnis: Implikasi Klinis dalam Terapi Individual - Fitri, Maghfiroti; Ananda, Dea; Hasanah, Rahmatun Nurul; Mardianti, Ririn (Pharmaceutical Journal, 2025)
Pharmacogenomics is a field that explores how genetic variations influence individual responses to drug therapy. One of the major challenges in its clinical application is the genetic diversity across ethnic groups, which contributes to differences in drug metabolism, efficacy, and toxicity. Genetic polymorphisms in enzymes such as CYP2D6, CYP2C19, CYP2C9, and VKORC1 show varied distributions among ethnic populations, leading to significant variation in optimal dosing and adverse drug reactions. This narrative literature review aims to examine the relationship between ethnic-specific genetic variation and drug response, while also assessing the potential of personalized pharmacogenomic therapy in clinical practice. Findings suggest that pharmacogenetic approaches that account for ethnic background can improve therapeutic outcomes, reduce adverse effects, and support the implementation of precision medicine across diverse healthcare systems, including in developing countries.